Wissen über die englische Stadt des 19. Jahrhunderts. Plurale Akteure empirischer Stadtforschung und ihre Vorgehensweisen. - Zimmermann, Clemens (Deutsches Institut für Urbanistik, 2021)
Der Beitrag diskutiert die Anfänge der Stadtforschung im englischen Kontext. Dafür werden die Forschungsprojekte von Friedrich Engels über die „Lage der arbeitenden Klasse“, speziell die Passagen zu Manchester (1845), sowie die Studien von Henry Mayhew (1861/62) und Charles Booth (1889-1897) zu London untersucht. Im Vordergrund stehen die jeweiligen Zielsetzungen und die angewandten Untersuchungsmethoden sowie das diesen Autoren zur Verfügung stehende Material. Welche Wissensbestände gingen in die publizierten Projekte ein, die wiederum ein besonderes Expertenwissen begründeten? In welcher Weise wurde das lokale Wissen der Stadtbewohner*innen in den Projekten verarbeitet und umgeformt? Diese Problemstellung knüpft an die Debatte über das Verhältnis von Wissenschaftsgeschichte und Wissensgeschichte an. Simone Lässig definiert Wissensgeschichte wie folgt: „The History of knowledge explores what people in the past understood by the idea of knowledge and what they defined or accepted as knowledge. It is concerned with the interaction of different types and claims to knowledge.“ Diesem Ansatz soll hier gefolgt werden – soweit das verfügbare Quellenmaterials dies ermöglicht.

This article reconstructs the research projects undertaken by Friedrich Engels on Manchester (1845) and by Henry Mayhew (1861/2) and Charles Booth (1889-1897) on London. The aim is to consider the diversity and scope of empirical knowledge about cities, and how the researchers dealt with this. This article will depart from existing presentations of Engels’ pioneering work „The Condition of the Working Class in England“ in order to investigate his own urban experience. It will show that Engels’ study assumes a variable, socially constructed space as an inherent part of social analyses. Mayhew continues to enjoy a reputation as a versatile reporter. His principal work, London Labour and the London Poor, received a great deal of public attention for the mass of colourful detail it shared. But how did Mayhew formulate the positions of his interview partners (from an anthropological perspective)? Booth ranks uncontroversially as a pioneer of modern urban research. The central problem here, however, is the extent to which one can process the prodigious amount of material to reconstruct the social experience of the subjects investigated. All three of the approaches rather closely arrived at what is today called participant observation.
Keywords: Stadtforschung; Stadtgeschichte; Stadtgeschichtsforschung; Sozialgeschichte; Forschungsmethode; Stadtbewohner; Wissensbasis; Stadtwissenschaft; Empirische Sozialforschung